Clinico-Hematological Profile of Anemia in Infants and Children - Sinha, Preeti; Kumar, Naveen (Student’s Journal of Health Research Africa, 2024)
Introduction: Anemia is characterized by decreased hemoglobin levels it is widely prevalent around the world. It is reported amongst women within 13-50 years of age group and among the pediatric population. It has severe health consequences and it affects the social and economic growth of the country as well. Material and Methods: This is an outpatient as well as inpatient department based Prospective Observational study among 100 patients with suspected anemias who are infants or children (up to the age of 14) attending the OPD and Emergency of Department of Paediatrics at Patna Medical College and Hospital, Patna. Results: In our study, 44% of the study participants were having IDA followed by ACD (17%). Dyserythropoiesis and Pure Red Cell Aplasia consist of 1% of the study population. In the infant and younger age group, IDA were most prominent type of anemia. However, in older age group 10-14 years, Aplastic anemia were the prominent type of anemia. Conclusions: Among 100 pediatric patients studied, Anemia was prevalent in children below 5 years. Children with a male preponderance aplastic anemia was most common among 10-14 years age group. For optimal treatment of anemia multiple facets should be addressed. An integrated approach can help in dealing with this disease.